MODELING THE MEASURING OF NARROWING DIGITAL DIVIDE IN INDONESIA (CASE STUDY : PUBLIC SENIOR HIGH SCHOOL IN BANDUNG CITY) - YULFITRI (NIM 23506001), ALIVIA
The information and communication technology (ICT) growth and its connection through internet had caused changes of activities and works in many levels of population. Starting from individuals, businesses, and the government had done changes in their activities and works. Individual, just by sitting in front of computer at his house, but he has able to do his work or capture informations from the world wide for various of needs, for example, to capture information about his work, products, services, health, education, job vacancies, news, etc. Business with its e-commerce could increase selling or expanding its business wider. Through the internet, the government could increase its service to public, thus made it possible to service with wider range that possibly may not be reached or even unreachable before. In this ICT growth rapidly, digital divide occurred. Digital divide concept is discussing about gap between individuals who had ICT access and those who hadn't, who had ICT skill effectively with individuals who hadn't. The ICT growth in Indonesia has owned 19 programs in its blue print and roadmap, which intended to increase the use of information and communication technology in Indonesia. Meanwhile, the digital divide in Indonesia is still very high. In order to achieve that purpose as a result, the narrowing digital divide research in Indonesia is needed to facilitate implementing ICT growth programs in Indonesia. The purpose of this research is to design the measuring model of narrowing digital divide in Indonesia, to design the level model of narrowing digital divide, and to propose strategy to narrowing digital divide in Indonesia. The measuring model is designed based on suitably to ICT condition in Indonesia and based on digital divide concept, by using indicators that match in Indonesia from indicators in SIBIS GPS instrument This research is performed to public high school teacher in Bandung City with analysis use correlation and double regression analysis. The research's result shown that internet readiness variable (X1), the usage of ICT (X2), the ICT skill acquisition (X3), and the ICT skill provision (X4) simultaneously influence to decrease digital divide (Y) is 21.7%, meanwhile the rest (78.3%) is determined by other variables outside the research. Then the increase or decrease score of narrowing digital divide can be predicted through regression equation Y=0.734 + 0.178 X1 + 0.258X2 + 0.213X3 + 0,353X4. The level model of narrowing digital divide that has been resulted is 4 (four) levels, which are : (1) unprepared, (2) limited preparation, (3) formalized preparation, and (4) mature preparation. Based on the score's calculation of narrowing digital divide at public senior high school teacher in Bandung City, it is resulted that the score is 0.7 which shown that the respondent had reached the third level. This level shown that the public senior high school in Bandung City had reached formalized condition. The result of condition analysis based on digital divide's variables that illustrated in 4 (four) quadrants shown that the public senior high school in Bandung City is still in the worst condition (quadrant IV) because of unavailability ICT access and teachers are still unable to use ICT completely and the ICT skill's level of the teacher is still unconfident yet. But, at the effort of ICT skill acquisition, the teachers had reached quadrant II, because 89 % of the teachers had acquired high effort even though the ICT access is unavailable. To solve the condition and the problem above, it is recommended 8 strategies which is expected can be applied to decrease digital divide in Indonesia.